PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJARSISWA KELAS IVB SD NEGERI 28 PEKANBARU - Nanda, Dwi Dian Beta Nanda Beta; Daud, Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this research is the low student learning outcomes IPS, it is seen from the average value of students is 63.6. Of the 25 students who achieve grades above KKM (Minimum Criteria for completeness) only 11 students (44%), while students who have not reached the KKM as many as 14 students (56%), the value specified KKM is the problem 75. based on classroom action research needs to be done by applying the Problem Based Learning Model This study aims to improve learning outcomes IPS IVB grade students of SD Negeri 28 Pekanbaru Academic Year 2014/2015 the number of students as many as 25 people consisting of 13 male students and 12 students women. This study was conducted by two cycles. I cycle consists of three meetings, which is twice the face to face meetings and one final repetition of the cycle. Cycle II consists of three face-to-face meetings and one final repetition of the cycle. With the implementation of Problem Based Learning model, it can improve student learning outcomes IPS, it is seen from the percentage of completeness of student learning outcomes on the basis that the score of 44% with an average of 63.6 increased in the first cycle with the average becomes 72.4 , In the cyclical II increased by average - 80 average. The percentage of teachers activity also increased, as seen from the percentage of teacher activity in the first cycle of 60% and a second meeting increased to 75% .Siklus II first meeting and the second meeting of the 85% increase to 90%. The percentage of student activity in the first cycle of 55% the second meeting increased to 70% in the first meeting of the second cycle of 80% and a second peretemuan increased again to 85% .From the above explanation can be seen that through the adoption of Problem Based Learning Model (PBM), can improve learning outcomes IPS fourth grade students of SD Negeri 28 B Pekanbaru. Key Words: Keywords: Application of Problem Based Learning Model Learning Outcomes IPS. Â